Exploring The Potential Of Digital Marketing For Msmes (Case Study: Young Coconut Traders In Ya'ahowu Park, Gunungsitoli) - Yuterlin Zalukhu (Journal of Management, Economic, and Accounting, 2025)
Taman Ya’ahowu is a culinary and entertainment center that has existed around ten years in Gunungsitoli City. At one end of the area, 30 micro-business actors sell fresh young coconuts, offering a unique coastal experience. However, most of these entrepreneurs still rely on conventional marketing methods. This study aims to analyze potential digital marketing strategies to enhance the competitiveness of young coconut micro-businesses. Data were collected through direct interviews with five business informants and Head of Trade Division, Department of Trade and Manpower at the Gunungsitoli City. The results show that only one of the five informants has utilized social media for marketing. This study provides recommendations for digital marketing strategies and empowerment steps for local micro-enterprises to expand market reach, foster customer loyalty, and strengthen business sustainability in the digital era.